Los ladrilleros, los perros y nosotros a la vera de un camino arrasado: Selva Almada (2013): Ladrilleros. Buenos Aires, Editorial Mar Dulce, pp. 232 - Iriart, Andrea (2014)
Fil: Iriart, Andrea. Grupo La Grieta.